2016
DOI: 10.1038/srep38489
|View full text |Cite
|
Sign up to set email alerts
|

Replicatively senescent human fibroblasts reveal a distinct intracellular metabolic profile with alterations in NAD+ and nicotinamide metabolism

Abstract: Cellular senescence occurs by proliferative exhaustion (PEsen) or following multiple cellular stresses but had not previously been subject to detailed metabolomic analysis. Therefore, we compared PEsen fibroblasts with proliferating and transiently growth arrested controls using a combination of different mass spectroscopy techniques. PEsen cells showed many specific alterations in both the NAD+ de novo and salvage pathways including striking accumulations of nicotinamide mononucleotide (NMN) and nicotinamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 57 publications
5
58
1
Order By: Relevance
“…NNMT methylates NAM to produce 1-MNA, thereby consuming SAM as a critical methyl source and increasing SAH (50,51). In human studies and animal models of oxidative stress, 1-MNA has been suggested to increase oxidative stress to promote antiinflammatory M2 polarization of macrophages, reduced proliferative exhaustion, and lifespan extension (70)(71)(72)(73). NNMT is required for low SAM levels and reduced histone methylation (histone 3 lysine 27 tri-methylation, H3K27me3) status in the epigenetic landscape of human embryonic stem cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…NNMT methylates NAM to produce 1-MNA, thereby consuming SAM as a critical methyl source and increasing SAH (50,51). In human studies and animal models of oxidative stress, 1-MNA has been suggested to increase oxidative stress to promote antiinflammatory M2 polarization of macrophages, reduced proliferative exhaustion, and lifespan extension (70)(71)(72)(73). NNMT is required for low SAM levels and reduced histone methylation (histone 3 lysine 27 tri-methylation, H3K27me3) status in the epigenetic landscape of human embryonic stem cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…An activation of the PPP has also been demonstrated in cancer cells, probably to produce more NADPH to combat oxidative stress [ 48 ]; indeed, the existence of PPP enzymes has been demonstrated in exosomes of ovarian cancer cells in proteomic analysis [ 37 ]. Human skin cells also activate the PPP in response to oxidative stress [ 49 ], and senescent fibroblasts show increased glycolysis and PPP to reduce ROS production, upregulation of pathways involved in redox homeostasis [ 50 ], and alterations in nicotinamide metabolism [ 51 ]. Moreover, another different metabolic possibility has been suggested for ROS scavenging; the enzyme biliverdin reductase has been involved in a ROS-scavenging mechanism in a subpopulation of epididymal fluid MVs, protecting spermatozoa against ROS released from dying cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since, NADP is mostly produced through the phosphorylation of NAD (Love et al, 2015), the decreased level of NADP may be related with previously reported alterations in NAD + metabolism in replicatively senescent human fibroblasts (James et al, 2016). However, no significant change was found in NAD + and NADH levels in SIPS fibroblasts while elevated levels of NADP were reported in replicatively senescent human fibroblasts (James et al, 2016). Another important metabolite for energy metabolism is Coenzyme A, the level of which was decreased by 4 fold in SIPS fibroblasts.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the overall level of NADP, which is a cosubstrate of both Glucose-6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase was decreased in SIPS fibroblasts (Figure 4C), arguing for a decreased efficiency of the pentose-phosphate pathway. Since, NADP is mostly produced through the phosphorylation of NAD (Love et al, 2015), the decreased level of NADP may be related with previously reported alterations in NAD + metabolism in replicatively senescent human fibroblasts (James et al, 2016). However, no significant change was found in NAD + and NADH levels in SIPS fibroblasts while elevated levels of NADP were reported in replicatively senescent human fibroblasts (James et al, 2016).…”
Section: Discussionmentioning
confidence: 73%